2021
DOI: 10.21037/gs-20-747
|View full text |Cite
|
Sign up to set email alerts
|

The influence of nodule size on the aggressiveness of thyroid carcinoma varies with patient’s age

Abstract: Background: Thyroid nodule size is one of the key parameters that determines the operative approach for thyroid carcinoma. It is necessary to evaluate the influence of nodule size on the aggressiveness of thyroid carcinoma. The eighth edition of staging system has updated the prognostic age cutoff from 45 to 55 years old. It is needed to re-evaluate the difference in aggressiveness of thyroid carcinoma between younger (<55 years old) and older (≥55 years old) patients. Importantly, whether the influence of nod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
(39 reference statements)
1
8
0
Order By: Relevance
“…Numerous studies have focused on the analysis of prognosis based on age stratification. Our previous research demonstrated that the effect of tumor size on the aggressiveness of PTC varied with the patient's age (23). Additionally, a study indicated that BRAF mutation was more common in PTC patients over 55 years old (24).…”
Section: Discussionmentioning
confidence: 98%
“…Numerous studies have focused on the analysis of prognosis based on age stratification. Our previous research demonstrated that the effect of tumor size on the aggressiveness of PTC varied with the patient's age (23). Additionally, a study indicated that BRAF mutation was more common in PTC patients over 55 years old (24).…”
Section: Discussionmentioning
confidence: 98%
“…In a recently done study, they did find that large nodule size is significantly related to a more aggressive thyroid cancer indicating unfavorable events. [ 9 ]…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent study based on two larger cohorts demonstrated that lymph node involvement was associated with compromised survival in young patients ( 18 ). Also, our previous study found that a large nodule size significantly increased the risk of unfavorable events in younger patients ( 19 ). The abovementioned results suggest that it is inappropriate to classify patients younger than 55 years without metastatic disease into uniform stage, and that stage II DTC in older patients and stage II DTC in younger patients are not equal in overall survival.…”
Section: Introductionmentioning
confidence: 88%